Pengaruh Komunikasi Bahasa Tubuh, Kualitas Produk dan Kualitas Pelayanan terhadap Loyalitas Pelanggan di CV. Malasari - Syati Manaharawan Siregar; Nur Ainun; Refli Renaldi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine how much influence body language communication, product quality and service quality have on customer loyalty at CV. Malasari and The results of the study show that partially the body language communication variable has a positive and significant effect on customer loyalty. The results of the study show that partially the product quality variable has a positive and significant effect on customer loyalty. The results of the study show that partially the service quality variable does not affect customer loyalty at CV. Malasari. The results of the study show that simultaneously the body language communication variable, product quality and service quality have a positive and significant effect on customer loyalty. The suggestion for the company is to optimize body language communication and existing product quality in order to maintain customer loyalty.